Improving the Product-Policy Development Process at PT SMI with Agile and Knowledge Management Framework - Arif Apriyadi; Achmad Ghazali (Eduvest - Journal of Universal Studies, 2025)
Policy agility is critical for infrastructure financing institutions like PT SMI, which faces delays in policy development due to centralized decision-making, poor communication, and inadequate knowledge transfer, hindering alignment with product timelines and RJPP 2024–2028 goals. This study investigates how integrating Agile and KM frameworks (SECI model, APO KM Framework) can mitigate these delays. Using mixed methods—qualitative interviews and quantitative APO KM Maturity assessments—the research identifies key gaps in PT SMI’s processes and proposes a combined Agile-KM approach. Findings reveal that Agile’s iterative cycles and KM’s knowledge-sharing mechanisms enhance policy-product alignment, with pilot projects demonstrating reduced bottlenecks. The study provides a scalable implementation plan, emphasizing cross-functional collaboration and centralized knowledge repositories. Implications suggest this framework improves PT SMI’s operational efficiency and offers a replicable model for similar institutions, bridging a gap in the literature on Agile-KM synergy in financial policy development.